Sosialisasi Produksi Pada Usaha Gula Merah (Aren) - Patrisia, Eka Salsa; Putra, Iswidana Utama; Putri, Lydia Gustina; Herlina, Yeni; Irwanto, Tito (Universitas Dehasen Bengkulu, 2024)
This research aims to identify and socialize production strategies in palm sugar businesses to increase efficiency and productivity. Socialization of this strategy was carried out involving palm sugar farmers, craftsmen and related stakeholders. The methods used include field observations, in-depth interviews, and evaluation. The research results show that by implementing more modern and efficient production techniques, as well as optimal use of resources, palm sugar businesses can improve product quality and production capacity. Apart from that, ongoing education and training on production and marketing management also supports the sustainability of this business. The conclusion of this research is that the socialization of appropriate production strategies can have a positive impact on increasing the competitiveness and welfare of palm sugar business actors.